1984
DOI: 10.1111/j.1471-0528.1984.tb04803.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of amniotic fluid in South Indian women

Abstract: Summary Samples of amniotic fluid obtained from 48 South Indian women in the third trimester of pregnancy were studied for antimicrobial activity. The growth of Staphylococcus albus, Candida albicans and Clostridium perfringens was inhibited by nearly all samples studied while the growth of Staphylococcus aureus, Escherichia coli and Bacteroides fragilis was inhibited by 50%, 42% and 18% of samples respectively. The growth of Streptococcus faecalis was not inhibited. Using radial immunodiffusion, IgG was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In multiple studies reported in the literature 18–73% of AF samples exhibited inhibitory properties towards various bacterial species. The antimicrobial properties depend on gestation stage and ethnicity [16], [17], [18], [19], [20]. Because individual specimens of AF can vary in their antimicrobial properties even towards GBS [21], we first tested the ability of the collected samples to support GBS growth.…”
Section: Resultsmentioning
confidence: 99%
“…In multiple studies reported in the literature 18–73% of AF samples exhibited inhibitory properties towards various bacterial species. The antimicrobial properties depend on gestation stage and ethnicity [16], [17], [18], [19], [20]. Because individual specimens of AF can vary in their antimicrobial properties even towards GBS [21], we first tested the ability of the collected samples to support GBS growth.…”
Section: Resultsmentioning
confidence: 99%